The Influence of Social Media Marketing Features on Consumers’ Purchasing Decisions of Tourism Products - Azizpuddin, Farah Nur Adilah Mohd; Shahrom, Melissa (Information Management and Business Review, 2024)
The prevalence of social media usage in Malaysia is apparent, as a substantial 78.5% of the population actively participates in online platforms. This provides the groundwork for an extensive analysis of the influence that social media marketing has on the decision-making process of consumers in the digital domain. This research focuses on analyzing the influence of four specific aspects of social media marketing on consumers’ purchasing decisions for tourism products. Interactivity, informativeness, entertainment value and perceived relevance are the elements that must be taken into account. The data was gathered from a diverse group of individuals who have extensive experience with social media. This was done through a thorough and structured online survey. The survey was completed by 142 participants in total and the data was analyzed using SPSS. The findings indicate that factors such as interactivity, informativeness and perceived relevance play a significant role in influencing consumers’ purchase decisions. However, it was discovered that the impact of entertainment on purchase decisions is not significant. The findings of this study make an important contribution toward filling the gap in exploring how the tourism industry maximizes social media marketing features as digital marketing in knowing consumers’ purchasing decisions. This study has shed some light on how marketers effectively manage and take advantage of social media platforms such as Instagram, Twitter, Facebook and Tik-Tok. Further research comparing with bigger data and other countries or regions will enrich the research findings.